Pengaruh Herbal Therapy Compress Ball Terhadap Nyeri Punggung BAWAH IBU HAMIL Trimester III DI PMB BDN. Komang Kristina Dewi, S. KEB.,S.K.M - Ni Luh Marnevi; Ni Made Egar Adhiestiani; Putu Mastiningsih (NERSMID : Jurnal Keperawatan dan Kebidanan, 2024)
Pregnancy is a physiological process that brings significant changes to the body, often causing discomfort such as lower back pain. Pain management is important for the comfort of pregnant women. Research Objectives: This study aims to evaluate the effectiveness of the Herbal Therapy Compress Ball in reducing lower back pain in third trimester pregnant women. Materials and Methods: Using a pre-experimental design One Group Pre-test Post-test , this study involved 49 pregnant women in the third trimester with low back pain, selected through purposive sampling. The intervention was carried out with a Herbal Therapy Compress Ball, and its effectiveness was measured using the Wilcoxon Test to analyze differences in pain levels before and after therapy. Research Results: Data analysis showed a decrease in the average level of lower back pain from 3.24 to 1.76 after applying Herbal Therapy Compress Ball. With a p-value of 0.000 (<0.05), there is a significant difference in the level of lower back pain in third trimester pregnant women after therapy. Conclusion: Herbal Therapy Compress Ball has been proven to be effective in reducing lower back pain in third trimester pregnant women. It is recommended for pregnant women in the third trimester to consider using this therapy as a non-pharmacological method for managing low back pain during pregnancy.